Nilai-Nilai Pendidikan Akhlak Dalam Film Animasi Adit dan Sopo Jarwo Episode 22 dan Episode 24 - Meifa Adinda Erwina; Syafei Syafei (Prodi Pendidikan Keagamaan Islam, 2022)
The problem of this research is the values ​​of moral education contained in the animated film Adit and Sopo Jarwo episode 22 and episode 24, looking at the good morals and bad morals contained in this animated film. This study aims to analyze the values ​​of moral education in the animated films Adit and Sopo Jarwo Episode 22 and Episode 24. This type of research is library research. One of the values ​​of moral education contained in the animated film Adit and Sopo Jarwo, is morals to Allah SWT such as: grateful, sincere and pleased with qada' and qadar Allah SWT. Morals to fellow human beings are simple, such as: help, patience, responsibility, greetings, courage. mazmumah morals such as lying, selfish, angry, khiyanat, al-jubn (cowardice). The results of the research in the animated films Adit and Sopo Jarwo Episode 22 and Episode 24 are expected to be a benchmark for all groups from children, teenagers, parents and provide a good spectacle to all mankind.